How does the emotive content of televised anti-smoking mass media campaigns influence monthly calls to the NHS Stop Smoking helpline in England? - Richardson, Sol; Langley, Tessa; Szatkowski, Lisa; Sims, Michelle; Gilmore, Anna; McNeill, Ann; Lewis, Sarah (Elsevier, 2014)
OBJECTIVE: To investigate the effects of different types of televised mass media campaign content on calls to the English NHS Stop Smoking helpline.